DEVELOPING POSITIVE QUALITIES OF YOUNG GENERATIONS, BASED ON IBN SINA' S KNOWLEDGE. - Sh.U.Kamolova (Scholar Express Journals, 2023)
This article is specific to today's globalization process, where the essence of the formation of positive qualities in the consciousness of IbnSina has melted
Keywords: medicine; harmoniously developed generation; educational process